2015
DOI: 10.1186/s12911-015-0209-8
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes of doctors towards e-health use in healthcare delivery in government and private hospitals in Northern Uganda: a cross-sectional study

Abstract: BackgroundE-health is an essential information sharing tool in healthcare management and delivery worldwide. However, utilization of e-health may only be possible if healthcare professionals have positive attitudes towards e-health. This study aimed to determine the relationships between healthcare professionals’ attitudes towards e-health, level of ICT skills and e-Health use in healthcare delivery in government and private hospitals in northern Uganda.MethodsCross-sectional survey design was used. Sixty-eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 38 publications
5
53
1
Order By: Relevance
“…Around two third of them, used smart devices in their daily clinical practice. The high frequency of Medical Apps installation and their use is consistent with Geoffrey et al, [18] which showed that majority of healthcare professionals, had positive attitude towards medical apps.. The prominent motivating factor behind adopting the Medical Apps among our studied population was found to be recommendations from their colleagues.…”
Section: Discussionsupporting
confidence: 88%
“…Around two third of them, used smart devices in their daily clinical practice. The high frequency of Medical Apps installation and their use is consistent with Geoffrey et al, [18] which showed that majority of healthcare professionals, had positive attitude towards medical apps.. The prominent motivating factor behind adopting the Medical Apps among our studied population was found to be recommendations from their colleagues.…”
Section: Discussionsupporting
confidence: 88%
“…The results were comparable with 92% of surveyed UK nurses used a computer at work daily and only 1% had never used the computer at work (Royal College of Nursing, 2015). On the other hand, our results were higher than that obtained by Olok et al who found that only 57.4% healthcare workers used a computer and 48.5 % used the internet facilities (Olok GT. et al, 2015).…”
Section: Discussioncontrasting
confidence: 56%
“…Participants further reported that keeping data is made easy, tracking information is simplified and access to variety of news, and disease and treatment information through internet is possible with ICTs. Study done by Olok et al [30] in hospitals in northern Uganda indicated that ICT could offer benefits in the delivery of health services. A senior health worker in one district highlighted some of the unique benefits of ICTs as below:

“I strongly believe that ICT will improve reading culture for the health workers which will improve the quality of health services in rural post-war and post-conflict northern Uganda.

…”
Section: Resultsmentioning
confidence: 99%